Emergency Medical Services Readiness and Operational Response to Terrorism Threats within Health Security Frameworks-An Updated Review - Alqahtani, Hind mohammed; Hind Mohammed Mujaddil Alqahtani; QASEM MOHAMMED KABSH; Saeed Shaya Abdullah Al-Dossary; Yousef Ali Huran Alanazi; Anwar Nawaf Alrashidi; Abdullah Madhyan Mubarak Al Mani; Mohammed Abdullah Mohammed Alwani; Ahmed Mania Ayed Alrashidi; Mastourah Nafea Muneer AL-Sehli; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Terrorism continues to pose a significant global threat, with evolving tactics that increasingly target civilian populations and infrastructure. These incidents generate complex mass casualty scenarios that place extraordinary demands on Emergency Medical Services (EMS). In addition to conventional blast, firearm, and stabbing injuries, modern terrorism encompasses chemical, biological, radiological, and nuclear (CBRN) threats, requiring expanded preparedness within health security frameworks. Aim: This review aims to examine the readiness and operational response of EMS to terrorism-related incidents, with a focus on injury patterns, responder safety, triage systems, interagency coordination, and the integration of tactical and CBRN response principles. Methods: A narrative review approach was used, synthesizing existing literature and operational experiences related to terrorism incidents. The article analyzes patterns of injury from explosive, firearm, vehicular ramming, and CBRN attacks, while evaluating established EMS response models, scene zoning, triage protocols, and tactical medical frameworks. Results: Terrorism-related incidents are associated with high injury severity, multidimensional trauma, and significant responder risk. Effective EMS response depends on scene security, structured zoning (hot, warm, and cold zones), rapid hemorrhage control, standardized triage protocols, and strong coordination with law enforcement and public health authorities. Tactical medical integration and specialized teams improve survivability while reducing responder harm. Conclusion: EMS preparedness for terrorism requires comprehensive planning, specialized training, and integrated command structures. Strengthening interagency coordination, tactical medical capability, and CBRN preparedness is essential to enhance system resilience, protect responders, and optimize patient outcomes in terrorism-related emergencies.